BPJS Drug Classification in Hypertension Category Using The ABC-VEN Method at Sinjai Regional Hospital for the Period April-June 2024 (International Forum of Researchers and Lecturers, 2025)
The procurement of pharmaceutical supplies must be managed both effectively and efficiently due to varying drug costs across different hospitals. An excessive supply can lead to medication spoilage, while inadequate stock levels can cause service interruptions and patient dissatisfaction. To optimize procurement, the ABC-VEN combination method serves as a valuable tool for evaluating hypertension drug inventory based on both cost value and criticality. This study was conducted to classify hypertension medications covered by BPJS at Sinjai Regional Hospital during the period of April to June 2024 using the ABC-VEN analysis method. This non-experimental research employed a descriptive retrospective approach, utilizing primary data through interviews and secondary data from the Drug Procurement Report (LPD). The ABC-VEN analysis revealed that category A drugs accounted for Rp. 18,120,000 (53.15%) of the total procurement cost, category B drugs amounted to Rp. 11,850,000 (34.75%), and category C drugs totaled Rp. 4,122,443 (12.1%). Based on the VEN classification, vital (V) drugs made up 28.57% (2 items), essential (E) drugs comprised 42.86% (3 items), and non-essential (N) drugs also represented 28.57% (2 items). The combination of ABC and VEN classification further identified that among the seven BPJS-funded hypertension drugs analyzed, priority (P) drugs accounted for 81.62% of the procurement value, followed by main (U) drugs at 21.48%, and complementary (T) drugs at 1.86%. These findings emphasize the importance of using ABC-VEN analysis to prioritize and manage hospital drug procurement effectively, ensuring both cost control and the continuous availability of essential medications for hypertension treatment.